Kosovo en el laberinto balcánico - Padrós, Lidia (Estudios Internacionales, 1998)
More than two years after the Dayton Accords (December 14, 1995), aspects never addressed reappear in the matter of the Balkan region. The Kosovar towns of Drenica, Decani and Stimilje, in the Federal Republic of Yugoslavia of Serbia and Montenegro (FRY), close to Albania, economically underdeveloped and socially organized into family clans, were repressed by the special police, the Army and the Serbian paramilitary militias. According to Pristina, the capital of Kosovo, these "ethnic cleansing" operations, which began in February 1998, have caused 1,472 deaths, including children and women, and 475,000 refugees and displaced persons, according to the latest December 1998 estimates from the United Nations High Commissioner for Refugees (UNHCR).